2015
DOI: 10.1016/j.jcp.2015.01.026
|View full text |Cite
|
Sign up to set email alerts
|

A general formulation of Bead Models applied to flexible fibers and active filaments at low Reynolds number

Abstract: This contribution provides a general framework to use Lagrange multipliers for the simulation of low Reynolds number fiber dynamics based on Bead Models (BM). This formalism provides an efficient method to account for kinematic constraints. We illustrate, with several examples, to which extent the proposed formulation offers a flexible and versatile framework for the quantitative modeling of flexible fibers deformation and rotation in shear flow, the dynamics of actuated filaments and the propulsion of active … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(102 citation statements)
references
References 86 publications
(207 reference statements)
17
85
0
Order By: Relevance
“…A recent review of these methods is found in [52]. In recent work [26] have elaborated upon basic bead models by introducing a new Lagrange multiplier method to impose constraints, and consider several flow problems -Jeffery orbits, buckling in shear, actuated swimming filaments -by using an approximate accounting of Stokesian hydrodynamics.…”
Section: G Bead-and-rod Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review of these methods is found in [52]. In recent work [26] have elaborated upon basic bead models by introducing a new Lagrange multiplier method to impose constraints, and consider several flow problems -Jeffery orbits, buckling in shear, actuated swimming filaments -by using an approximate accounting of Stokesian hydrodynamics.…”
Section: G Bead-and-rod Modelsmentioning
confidence: 99%
“…They also addressed the role of rotational diffusion on the period of Jeffery orbits. Numerous investigations have observed the "snaking" dynamics numerically ( [26,97,131]) (see Fig. 4c).…”
Section: Fiber Morphology In Shear Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second term on the right-hand side of the relation ( 20) describes the coupling of the twist with the writhe of the rod, which characterizes the formation of the loops. In the cases of the ferromagnetic and superparamagnetic rods when the magnetic energy terms are 3 …”
Section: Introductionmentioning
confidence: 99%
“…A central aspect of all of these examples is that the relevant dynamics is collective and not well-described by the dynamics of a single fiber.Given the importance of fluid-fiber systems, specialized computational methods have been developed to treat them, most especially in the zero Reynolds limit where flows are governed by the Stokes equation. These approaches include the use of nonlocal slender body theory [28,39], the immersed boundary method [19,29,33,37], bead-spring or -rod models [9,13,22,38], the regularized Stokeslet method [3,7,32,35], and overlapping grid methods [23]. See [20] for a recent review.…”
mentioning
confidence: 99%